PERAN PERPUSTAKAAN MASJID DALAM MENUMBUHKAN BUDAYA BACA MASYARAKAT DAN TRANSFORMASI ILMU PENGETAHUAN - Daryono Daryono (Jurnal Pustaka Ilmiah, 2017)
The mosque library has the main task that is to encourage the creation of the atmosphereof the life of the congregation into a society that has a culture of iqra ‘(read) is animplementation of Surat Al-Alaq verses 4 and 5. To support the task poko, the LibraryMasjid must implement several important roles owned by the library of mosques inorder to foster interest in reading and transformation of knowledge to the public.The role that is owned by the Library Mosque, among others: 1). As an Agency orintermediary of information to the community or mosque congregation. 2). As MediaTransformation and dissemination of information or science to society and 3). As aprovider of cheap information for the community.